New biflavonoids with α-glucosidase and pancreatic lipase inhibitory activities from boesenbergia rotunda - Nutputsorn Chatsumpun (2018)
©2017 by the authors.Licensee MDPI, Basel, Switzerland. Roots of Boesenbergia rotunda (L.) Mansf. are prominent ingredients in the cuisine of several Asian countries, including Thailand, Malaysia, Indonesia, India, and China. An extract prepared from the roots of this plant showed strong inhibitory activity against enzymes α-glucosidase and pancreatic lipase and was subjected to chromatographic separation to identify the active components. Three new biflavonoids of the flavanone-chalcone type (9, 12, and 13) were isolated, along with 12 known compounds. Among the 15 isolates, the three new compounds showed stronger inhibitory activity against α-glucosidase than the drug acarbose but displayed lower pancreatic lipase inhibitory effect than the drug orlistat. The results indicated the potential of B. rotunda roots as a functional food for controlling after-meal blood glucose levels.